2014
DOI: 10.1111/scs.12145
|View full text |Cite
|
Sign up to set email alerts
|

Room for caring: patients' experiences of well‐being, relief and hope during serious illness

Abstract: Our findings highlight aesthetic sensory impressions in the form of nature sights and natural light in the patient room as a powerful source of well-being, relief and hope for the patients during serious illness. Therefore, these sensory impressions should be thought of as holding palliative potential and should be included as a part of caring for the seriously ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…One of the obvious but often overlooked factors in clinical room design is the importance of aesthetics in patient rooms to aid healing. Timmermann et al () look at how seriously ill hospitalised patients’ experience and assign meaning to their patient room. They describe how, in open wards, while there may be a lot of technical equipment around, there is also a lot of activity to act as a distraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the obvious but often overlooked factors in clinical room design is the importance of aesthetics in patient rooms to aid healing. Timmermann et al () look at how seriously ill hospitalised patients’ experience and assign meaning to their patient room. They describe how, in open wards, while there may be a lot of technical equipment around, there is also a lot of activity to act as a distraction.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies in this review were from international healthcare systems. Two of the studies used patient interviews (Tan et al, ; Timmermann et al, ) with the latter also collecting some observational data. The other two studies sought the views of both patients and staff, but this was focused on a very explicit intervention (Bradley & Mott, ; Persson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Timmermann et al . () shows that ‘moments of presence’ (e.g. experiences of time standing still) allow patients to feel a sense of relief when hospitalized.…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 99%
“…Our study showed that they had the power to create a moment of rest and, at the same time, an experience of possibilities. The study by Timmermann et al (2015) shows that 'moments of presence' (e.g. experiences of time standing still) allow patients to feel a sense of relief when hospitalized.…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 99%